Safeguarding the child athlete in sport: a review, a framework and recommendations for the IOC youth athlete development model - Mountjoy, M.; Rhind, D. J. A.; Tiivas, A.; Leglise, M. (British Journal of Sports Medicine, 2015)
Participation in sport has many physical, psychological and social benefits for the child athlete. A growing body of evidence indicates, however, that sport participation may have inherent threats for the child`s well-being. The subject of safeguarding children in sport has seen an increase in scientific study in recent years. In particular, there is increasing emphasis on identifying who is involved in abuse, the context of where it occurs and the identification of the various forms of abuse that take place in the sporting domain. Safeguarding principles developed by the International Safeguarding Children in Sport Founders Group are presented along with 8 underlying pillars which underpin the successful adoption and implementation of safeguarding strategies. This safeguarding model is designed to assist sport organisations in the creation of a safe sporting environment to ensure that the child athlete can flourish and reach their athletic potential through an enjoyable experience. The aim of this narrative review is to (1) present a summary of the scientific literature on the threats to children in sport; (2) introduce a framework to categorise these threats; (3) identify research gaps in the field and (4) provide safeguarding recommendations for sport organisations.